A CRITICAL DISCOURCE ANALYISIS ON BARACK OBAMA FARAWELL ADRESS AT CHICAGO - Pasande, Priskila Ekawati Anggana; Arifin, M. Bahri; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
The area of this research is critical discourse analysis using the characteristics of the microstructure, superstructure, and macrostructural approaches by Van Dijk's theory. The object behind the research is Barack Obama last speech during his tenure as president of the United States, which was held on January 10, 2017 at McCormick Place, Chicago, IIIinois. In his last speech, Barack Obama expressed his gratitude to those who have been very supportive. He is during his tenure as president. In his speech, Barack Obama also discussed a lot about his message to the youth of the United States to be more active in contributing to the progress of the United States, and discussed a lot about the social and economic problems of the United States. Public Speaking by Barack Obama deserves to be studied and his clear and systematic way of speaking is the reason for researchers to research it, to find out what ideology is conveyed in his speech. This research focused on identifying the characteristics of the microstructure, superstructure, macrostructure, and ideologycal approaches contained in Barack Obama speech using a qualitative approach method. The results of this study indicate that ideologies of liberalism and ideologies of socialism. From these data, the researcher found that the ideology of liberalism was mostly contained in Barack Obma speech.